Effect of Human Myotubes-Derived Media on Glucose-Stimulated Insulin Secretion. (14th February 2017) - Mizgier, Maria L.; Cataldo, Luis R.; Gutierrez, Juan; Santos, José L.; Casas, Mariana; Llanos, Paola; Contreras-Ferrat, Ariel E.; Moro, Cedric; Bouzakri, Karim; Galgani, Jose E.
Abstract : Fasting to postprandial transition requires a tight adjustment of insulin secretion to its demand, so tissue (e.g., skeletal muscle) glucose supply is assured while hypo-/hyperglycemia are prevented. High muscle glucose disposal after meals is pivotal for adapting to increased glycemia and might drive insulin secretion through muscle-released factors (e.g., myokines). We hypothesized that insulin influences myokine secretion and then increases glucose-stimulated insulin secretion (GSIS). In conditioned media from human myotubes incubated with/without insulin (100 nmol/L) for 24 h, myokines were qualitatively and quantitatively characterized using an antibody-based array and ELISA-based technology, respectively. C57BL6/J mice islets and Wistar rat beta cells were incubated for 24 h with control and conditioned media from noninsulin- and insulin-treated myotubes prior to GSIS determination. Conditioned media from insulin-treated versus nontreated myotubes had higher RANTES but lower IL6, IL8, and MCP1 concentration. Qualitative analyses revealed that conditioned media from noninsulin- and insulin-treated myotubes expressed 32 and 23 out of 80 myokines, respectively. Islets incubated with conditioned media from noninsulin-treated myotubes had higher GSIS versus control islets ( p < 0.05 ) . Meanwhile, conditioned media from insulin-treated myotubes did not influence GSIS. In beta cells, GSIS was similar across conditions. In conclusion, factors being present in noninsulin-stimulated muscle cell-derived media appear to influence GSIS in mice islets.